Honey and Its Uses in the Home - Hunt, Caroline Louisa; Atwater, Helen W (United States. Department of Agriculture, 1915)
Informational pamphlet on honey includes a description of how honey is produced, its value as a food, the flavor of honey, its health benefits, its economy, household uses, and how it can be used in cooking. Contains recipes for bread, muffins, cakes, cookies, desserts, preserved fruits, icing, sauces and candies.
Keywords: Honey; Cooking; Hunt, Caroline Louisa, 1865-1927; Atwater, Helen W.; Cookbooks; United States. Department of Agriculture; Recipes